The Relationship of Culture with Education: Conceptual Analysis Study of Efforts to Eliminate the Negative Impact of the Rapid Development of Science and Technology on the Quality of Student Education - yayat suryatna (Edueksos Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTEducation is an effort to change human mindset, character and competence towards a better life through teaching and training. Education is a civilizing process, namely instilling values and norms in the life order of the nation and state, making human beings virtuous, noble and cultured beings. In the midst of advances in science and technology, especially transportation and information technology, human culture is also experiencing very rapid development. The cultural invasion from various parts of the world was so massive, both positive and negative cultures. This research is qualitative research using the library research method, by searching and collecting research data in the form of selected, searched, presented and analyzed library data. The source of this research data is to look for library data whose substance requires philosophical and theoretical action. From these sources, the researcher then analyzed the results of the study through the following stages: collection, grouping, analysis, interpretation, and presentation of data. Based on the data analysis, the researchers concluded that in order to minimize the negative impact of this cultural invasion on the quality of student education, there are several things that must be done, namely: 1) The importance of parental supervision of their children's use of cellphones; 2) The rules of conduct in each school should also regulate the use of cellphones; 3) The government should make regulations that prohibit access to sites that lead to negative things such as porn sites, online games, online gambling, be firm in imposing sanctions on creators and spreaders of negative content, create technology capable of blocking negative sites; 4) Society must also be sensitive to negative things that happen around them, don't be indifferent.Keywords:Culture, education and science and technology.